Escuta ativa de depoimentos: uma proposta pedagógica para o desenvolvimento da competência comunicativa oral - Carneiro, Cacilda Silva Oliveira (2016)
This educational intervention proposal is the product of Course Completion performed in the scope of the Professional Master of Arts (PROFLETRAS) of the State University of Feira de Santana (UEFS). It consists of applying listening activities of formal and informal testimonials in order to promote reflection on the language and contribute to the development of oral communication skills of the students, so necessary for the socio-affective practice of the individual. These reflections also undergo retextualization activities, they discuss themes such as linguistic diversity and the relations between speech and writing in an approach that represents an improvement when considering the guidelines introduced by the textbooks. The proposal in question is based on the design of interactive language - dialogue space that enables social practice of all kinds of acts - contrary to the approach of orality in the classroom as an excuse to practice reading and writing Marcuschi (1997, 2005a , 2005b); Marcuschi and Dionísio (2007); Dolz; Schneuwly (2004); Bentes (2010); BRAZIL (1997, 1998); Oliveira (2012); Bortoni-Ricardo (2004), Bronckart (2003); Machado (2007). The didactic sequence (DS) - structured in modules - was applied to a group of 6th grade of elementary level from a public school of São Domingos in the state of Bahia, during the period of two months, totalizing 26h/classes. The material obtained in the DS and analyzed in this work - audio, video and written texts – were obtained from the study subjects. The results of the intervention point that working with oral communication in the classroom, from the active listening texts, is productive and that the choice of testimony genre sparked interest and developed the creativity of students, becoming apparent in their productions, their progress regarding the oral competence. It is believed that if the DS were applied in greater time it would give more significant results. The research material is available in a repository for those who are interested in the discussions on the teaching of orality and concerned about the development of the oral competence of their students. The idea is that the proposal presented here add to other orality teaching proposals specifically, and mother tongue teaching, more broadly, in order to improve basic education and the life quality of students, expanding their communicative competence and making them, therefore, able to move around within the society without difficulty, mastering the resources and language mechanisms, understanding the meanings and senses that come to her.